miR319, miR390, and miR393 Are Involved in Aluminum Response in Flax (Linum usitatissimum L.) - Dmitriev, Alexey A. (Biomed Res Int, 2017)
Acid soils limit agricultural production worldwide. Major reason of crop losses in acid soils is the toxicity of aluminum (Al). In the present work, we investigated expression alterations of microRNAs in flax (Linum usitatissimum L.) plants under Al stress. Flax seedlings of resistant (TMP1919 and G1071/4_k) and sensitive (Lira and G1071/4_o) to Al cultivars and lines were exposed to AlCl(3) solution for 4 and 24 hours. Twelve small RNA libraries were constructed and sequenced using Illumina platform. In total, 97 microRNAs from 18 conserved families were identified. miR319, miR390, and miR393 revealed expression alterations associated with Al treatment of flax plants. Moreover, for miR390 and miR393, the alterations were distinct in sensitive and resistant to Al genotypes. Expression level changes of miR319 and miR390 were confirmed using qPCR analysis. In flax, potential targets of miR319 are TCPs, miR390–TAS3 and GRF5, and miR393–AFB2-coding transcripts. TCPs, TAS3, GRF5, and AFB2 participate in regulation of plant growth and development. The involvement of miR319, miR390, and miR393 in response to Al stress in flax was shown here for the first time. We speculate that these microRNAs play an important role in Al response via regulation of growth processes in flax plants.